2005
DOI: 10.1177/1045389x05055279
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Power Harvesting using a Tuned Auxiliary Structure

Abstract: Future, self-contained sensors and processing units will need onboard, renewable power supplies to be truly autonomous. One way of supplying such power is through energy harvesting, a process by which ambient forms of energy are converted into electricity. One energy harvesting technique involves converting kinetic energy, in the form of vibrations, into electrical energy through the use of piezoelectric materials. This study examines the use of auxiliary structures, consisting of a mechanical fixture and a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 12 publications
0
65
0
Order By: Relevance
“…The performance of the proposed harvester is compared to the results of existing research studies which implement their harvesters in a cantilever system under a similar range of excitation frequency and acceleration. The existing research works [35][36][37][38][39][40][41][42] produced a volume power density of (0.9 × 10 −2 -20 × 10 −2 ) µW/mm 3 under the excitation frequency of (1.4-100) Hz and the acceleration of (0.2-10) ms −2 . The current work produces a power density of 0.10 µW/mm −3 at a frequency and acceleration of 30 Hz and 0.4 ms −2 , respectively.…”
Section: Resistance (Kω)mentioning
confidence: 99%
“…The performance of the proposed harvester is compared to the results of existing research studies which implement their harvesters in a cantilever system under a similar range of excitation frequency and acceleration. The existing research works [35][36][37][38][39][40][41][42] produced a volume power density of (0.9 × 10 −2 -20 × 10 −2 ) µW/mm 3 under the excitation frequency of (1.4-100) Hz and the acceleration of (0.2-10) ms −2 . The current work produces a power density of 0.10 µW/mm −3 at a frequency and acceleration of 30 Hz and 0.4 ms −2 , respectively.…”
Section: Resistance (Kω)mentioning
confidence: 99%
“…Cornwell et al [51] adjusted various mechanical parameters, including the resonant frequency and the location of a harvester, to maximize the strain induced in the piezoelectric element and to improve power output. The power generation was increased by a factor of 25, if the frequency of the harvesting device was well-tuned to that of a structure.…”
Section: Energy Reservoirs Scavenged Power Sourcesmentioning
confidence: 99%
“…al have concluded that power generation through walking can easily generate power when needed, and 5-8W of power may be recovered 1 Values are estimates from literatures, analyses and few experiments; Values are highly dependent on amplitude and frequency of the driving vibrations 2 There were already many successful vibration harvesting devices reported of different structures and interface circuits [7,16,17]. Piezoelectric material that has been found to have the ability to convert vibration energy to electric power has sparked much attention as it was attractive for use in MEMS applications [16,18,19,20,21,22].…”
Section: Literature Reviewmentioning
confidence: 99%